Pro SQL Server Disaster Recovery - Luetkehoelter, James (Apress, 2011)
As Today's businesses become increasingly reliant on the information they store in their various databases, so the effective protection of that data becomes ever-more critical. Potential disasters can arise from natural causes like floods and hurricanes, to user errors, to media or hardware failure. The process of disaster recovery involves mitigating the likelihood of a disaster and the process of returning the system to a normal state. It is intricately linked with the important areas of availability and business continuity—which ensure day-to-day activities can continue regardless of the problem.